1956
DOI: 10.2307/1539010
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Metabolism and Morphogenesis During Regeneration in Tubifex Tubifex. Ii

Abstract: Analysis of the relations between metabolism and morphogenesis requires that each set of processes be separated into component parts. Metabolism may be fractionated by means of agents of which the effects on particular enzyme systems are reasonably well known and the relation of the activity of such systems to morphogenesis may then be tested. In the annelid, Tubifc.r tubijcx, morphogenesis during posterior regeneration may be measured fractionally and "rate of localization," "rate of early differentiation," a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1963
1963
1989
1989

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The relationship between morphogenetic changes during regeneration and the metabolic processes involved in tissue reconstitution have received attention from Anderson (see Collier, 1947 ; Anderson, 1956). Tubtfex tuhifex was found to respire at a rate of 0-16 ml/g wet wt.…”
Section: Metabolism In Regenerationmentioning
confidence: 99%
“…The relationship between morphogenetic changes during regeneration and the metabolic processes involved in tissue reconstitution have received attention from Anderson (see Collier, 1947 ; Anderson, 1956). Tubtfex tuhifex was found to respire at a rate of 0-16 ml/g wet wt.…”
Section: Metabolism In Regenerationmentioning
confidence: 99%
“…1951;Walker, 1955). Anderson (1956) found that exposure to one atmosphere oxygen pressure for ten days is lethal to T. tubifc.r and also inhibits regeneration ; 10~ 5 M cyanide stimulates some phases of regeneration. When regenerating worms are exposed to one atmosphere oxygen pressure in the presence of cyanide, survival is enhanced and the inhibition of regeneration by oxygen is partially reversed (Anderson, 1956V The blood of T. tubife.v contains hemoglobin in solution which lias an extremely high affinity for oxygen (Fox, 1945).…”
mentioning
confidence: 99%